Let $\lambda$ be the Lebesgue measure restricted to measure space $((a,b],\mathcal{B}(a,b])$, called $S$.

Let $\mathcal{F}_{(a,b]}$ be the collection of finite unions of half-open intervals in $S$.

Let $$\mathcal{A} = \{A\in\mathcal{B}((a,b]):\forall\epsilon >0\exists F\in \mathcal{F_{(a,b]}\text{ such that }\lambda(A\triangle F)<\epsilon\}}$$

Assume that $(A_n)_{n\geq 1}$ is a disjoint sequence in $\mathcal{A}$. Use the fact that if $\bigcup\limits_{n=1}^\infty A_n = A$ and $\bigcup\limits_{n=1}^\infty B_n=B$ then $A\triangle B \subseteq \bigcup\limits_{n=1}^\infty (A_n \triangle B_n)$, to show that $\bigcup\limits_{n=1}^\infty A_n \in \mathcal{A}$.

Question: How do I solve this exercise? Isn't it trivial that $\bigcup\limits_{n=1}^\infty A_n \in \mathcal{A}$, if $(A_n)_{n\geq 1}$ is a disjoint sequence in $\mathcal{A}$?

Thanks in advance!


Let $\epsilon>0$.

We have $\sum_{n=1}^{\infty}\lambda(A_n)=\lambda(A)\leq \lambda((a,b])=b-a$ so for $m$ large enough $\sum_{n=m+1}^{\infty}\lambda(A_n)<\epsilon2^{-1}$.

For every $n\leq m$ let $F_n\in\mathcal F_{(a,b]}$ such that $\lambda(A_n\Delta F_n)<\epsilon2^{-n-1}$ and for every $n>m$ let $F_n=\varnothing$.

Then $F=\bigcup_{n=1}^{\infty}F_n\in\mathcal F_{(a,b]}$ and we claim that $\lambda(A\Delta F)<\epsilon$.

For this observe that $A\Delta F\subseteq\bigcup_{n=1}^{\infty}(A_n\Delta F_n)$ so that: $$\lambda(A\Delta F)\leq\sum_{n=1}^{\infty}\lambda(A_n\Delta F_n)=\sum_{n=1}^{m}\lambda(A_n\Delta F_n)+\sum_{n=m+1}^{\infty}\lambda(A_n)<\sum_{n=1}^{m}\epsilon2^{-n-1}+\epsilon2^{-1}\leq\epsilon$$

This can be done for every $\epsilon>0$ so proves that $A\in\mathcal A$.

| cite | improve this answer | |
  • $\begingroup$ How do you know that $\sum_{n=1}^\infty \lambda(A_n) = \lambda(A)$? And why does $\lambda(A)\leq b-a$ imply that for $m$ large enough $\sum_{n=m+1}^\infty \lambda(A_n) < \epsilon 2^{-1}$? $\endgroup$ – titusAdam Jan 6 '18 at 10:37
  • $\begingroup$ The set $A_n$ are disjoint measurable and $A=\bigcup_{n=1}^{\infty}A_n$. Then $\lambda(A)=\sum_{n=1}^{\infty}\lambda(A_n)$ because $\lambda$ is a measure hence is $\sigma$-additive. $\sum_{n=1}^{\infty}\lambda(A_n)=\lambda(A)<\infty$ means that $s_m:=\sum_{n=1}^{m}\lambda(A_n)\to\lambda(A)$. Then $\sum_{n=m+1}^{\infty}\lambda(A_n)=\lambda(A)-s_m\to0$. $\endgroup$ – drhab Jan 6 '18 at 12:10

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.